Pengaruh Pembelajaran STEAM terhadap Peningkatan Pemahaman Konsep Sistem Peredaran Darah Manusia pada Siswa Kelas V - Alam Gymnastiar; Ali Ismail; Cucun Sunaengsih (Journal on Education, 2024)
Understanding concepts is a basic ability that students must master. However, in reality, not all students have a good understanding of the concept. This research aims to determine the effect of STEAM learning on increasing understanding of the concept of the human circulatory system in grade V elementary schools. The method used is a quasi-experimental method using a nonequivalent control group design. This research was conducted in two elementary schools in Situraja sub-district. The samples used in this research were 28 students in the control class and 28 experimental classes. The instrument in this study used an observation guide test. The results of this research show that the implementation of STEAM learning has very good criteria seen from the results of the teacher's worksheet and student activities. Students' conceptual understanding before STEAM learning received a student score including the very poor criteria. After STEAM learning, students' conceptual understanding was included in the sufficient criteria, this shows an increase in students' conceptual understanding. STEAM learning has the effect of improving students' ability to understand concepts, besides that STEAM learning is better than conventional learning. STEAM learning has an impact on students and teachers regarding experiences in using technology in learning.